Improvement of odor, flavor and color of Mongo bean powder (Phaseolus aureus Roxb.) - Cruz, Susana B.
It was found that a preliminary wash with 95% ethanol is necessary in order to obtain protein and flour from mongo beans freed mostly from its objectionable features. This protein in mongo can be extracted by treatment of the finely ground (100-mesh) sample with dilute NaOH solution at a 1:10 ratio, (pH 7.5). the protein concentrate obtained can be used as a base in dehydrated infant food or breakfast foods, soups or other applications in the food industry, while the deproteinated residue can be used as flour. The original flour obtained after alchohol washing has a high whipping powder and can be used in cakes and ice cream mxies. Steam distillation failed to remove the characteristics green color and beany odor. Studies indicate that the oil obtained by alcohol extraction contains most of the materials responsible for the undesirable features. Roasting at 250℃ until brown improve the flavor, but the whipping power was completely lost.